An experimental framework for simulating stress corrosion cracking in cable bolts. (June 2018) - Wu, Saisai; Chen, Honghao; Craig, Peter; Ramandi, Hamed Lamei; Timms, Wendy; Hagan, Paul C.; Crosky, Alan; Hebblewhite, Bruce; Saydam, Serkan
Abstract: Stress corrosion cracking (SCC) of cable bolts in underground mines is a universal issue with limited cost effective solutions at present. Understanding the SCC mechanism of cable bolt failure is crucial in maintaining effective ground support and hence increasing the safety and productivity of underground mines. However, to date, no practical laboratory system has been developed to replicate the SCC mechanism which occurs in underground mines. In this study, based on the chemical properties of mine water, an acidified solution containing sulphide is synthesized. The solution is exposed to the wire strands from cable bolt in the laboratory to model service failure. It is shown that the applied stress intensity and time to failure have an inverse power law relationship in wires of cable bolts. Similar features are observed in both laboratory-failed specimens and the service-failed cable bolts under macroscopic and microscopic examinations, demonstrating the ability of the proposed framework to simulate failure of cable bolt subjected to SCC in the laboratory. Furthermore, the impact of stress intensity and hydrogen concentration on SCC are examined and a cohesive failure mechanism on the cable bolt SCC crack initiation, growth and catastrophic failure are presented. The proposed framework can be applied to the reinforcement materials for improved understanding of the SCC mechanism in underground mines and tunnels.